Federal Policy Towards State and Local Economic Development in the 1990s - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 1993)
This paper suggests new federal policies towards state and local economic development assistance to business. I argue that there is some evidence that these programs can be effective in encouraging business growth and helping the unemployed. But state and local governments do not have the right incentives to adequately pursue national goals through economic development programs. State and local governments are not inclined to do quality evaluations of their programs and tend to favor business attraction programs over programs that might increase U.S. business productivity. In addition, it is unclear whether economic development efforts are most vigorously pursued by economically depressed areas, in which the national social benefits of economic development are the greatest. A new federal policy towards economic development should provide partial federal support for state and local economic development programs that encourage business productivity. The funding should be coupled with requirements for rigorous outside evaluation, comparing the performance of assisted and unassisted firms. Finally, our system of fiscal federalism should be reformed to provide greater resources for economically depressed areas. This assistance will allow these areas to be more economically competitive.
Additional information: A revised version of this paper appears in R. Ebel and R. Norton, eds,. 1993. Research in Urban Economics: (Vol. 9) Structuring Direct Aid: People versus Places. Greenwich, CT: JAI Press, pp. 161-178.
Keywords: R0; J4; 330; state; local; economic; development; Bartik